Pilot-scale tests to optimize the treatment of net-alkaline mine drainage - Jang, M.; Kwon, H. (2011)
A pilot-scale plant consisting of an oxidation basin (OB), a neutralization basin (NB), a reaction basin (RB), and a settling basin (SB) was designed and built to conduct pilot-scale experiments. With this system, the effects of aeration and pH on ferrous oxidation and on precipitation of the oxidized products were studied systemically. The results of pilot-scale tests showed that aeration at 300 L/min was optimum for oxidation of Fe(II) in the OB, and the efficiency of oxidation of Fe(II) increased linearly with increasing retention time. However, Fe(II) was still present in the subsequent basins-NB, RB, and SB. Results from pilot-scale tests in which neutralization was excluded were used to obtain rate constants for heterogeneous and homogeneous oxidation. Oxidation of Fe(II) reached almost 100 when the pH of the mine drainage was increased to more than 7.5, and there was a linear relationship between total rate constant, log (K total), and pH. Absorbance changes for samples from the NB under different pH conditions were measured to determine the precipitation properties of suspended solids in the SB. Because ferrous remained in the inflow to the SB, oxidation of Fe(II) was dominant initially, resulting in increased absorbance, and the rate of precipitation was slow. However, the absorbance of the suspension in the SB rapidly dropped when pH was higher than 7.5. Â© 2010 Springer Science+Business Media B.V.